Synthesis and characterization of alkyl-methacrylate-maleic anhydride copolymer for use as a biodiesel flow improver - Ngoc Lan Pham; Van Boi Luu; Thi Tuyet Mai Phan; Thi Son Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
Due to its many advantages such as renewable raw materials and small negative impact on the environment, biodiesel has the most potential as an alternative to petro-diesel. However, one weakness of biodiesel is due to its origin of vegetable oil or animal fat. This is because during the cold season, when the ambient temperature is lower than 15oC, the viscosity of biodiesel increases and produces precipitation that causes difficulties for engine operation. Methacrylic acid was esterified with four alcohols: 1-decanol, 1-dodecanol, 1-tetradecanol, and 1-cetanol. Afterwards, the obtained monomers were copolymerized with maleic anhydride. The synthesized monomers and copolymers were characterized by 1H-NMR (Nuclear magnetic resonance) and Fourier transform infrared (FTIR) spectroscopy. The ability of the obtained copolymers to reduce the pour point of waste cooking oil- based biodiesel was investigated. The results showed that the polymer additive with the alkyl chain C14H29- demonstrated the best flow improvement performance. At a concentration of 1000 ppm, this polymer additive reduced the pour point of waste cooking oil-based biodiesel from 12 to 5oC. In this study, the effect of alkyl chain length, molecular weight, as well as the concentration of the additives on the pour point of biodiesel was also discussed.